From Progressive Radicalism to Democratic Degeneration: The Trajectory of John Locke's Political Theory - Karimi, Sirvan (International Journal of Law and Public Policy (IJLAPP), 2021)
As an organic intellectual of the emerging propertied class in 17th century England, John Locke has made an enduring contribution to the prevailing ideas shaping the socio-political order in Western societies and beyond. Through invoking the law of nature and natural rights which were nothing more than what he had abstracted from the socio-economic conditions of the seventeenth century and had projected back into the state of nature, Locke assiduously embarked on justifying the separation of civil society from the state, naturalizing class inequalities identifying the preservation of property as the fundamental function of the state, and rationalizing the subordination of propertyless classes to the emerging liberal democratic political order geared to preserve the interests of economically hegemonic classes.